PROBLEMATIKA PEMBELAJARAN AL-QUR’AN HADITS UNTUK MI/SD - Argista (Al Ulya: Jurnal Pendidikan Islam, 2021)
This study aims to identify the problem of learning Al-Qur'an Hadis in MI. The process used in this article is library research. The method of collecting information in this research is documentation. Documents, which dig up information in the form of paper notes, articles, etc. The results of the study indicated that there were problems, among others, students who could not recite verses of the Koran according to the principles of tajwid because their background and the level of learning of Al-Qur’an Hadis teachers had not improved. Learning facilities / equipment are still limited. Solutions to the problem of learning Al-Qur’an include practicing reciting the Al-Qur’an and how to skillfully teach the Al-Qur’an, applying the learning method of learning the Koran for new students, as well as applying the Al-Qur’an, implementing tadarus, obtaining learning resources, providing guidance to students and provide guidance to parents of students.